Pengelolaan Keuangan BLUD Puskesmas dan Rumah Sakit di Kabupaten Sidrap - Syamsuddin, Syamsuddin; Amiruddin, Amiruddin; Natsir, Andi Iqra Pradipta; Utami, Rizky; Haerial, Haerial; Nugraha, Rakhmat Nurul Prima; Indrijawati, Aini; Alam, Ade Ikhlas Amal; Putri, Anissa Aulya; Nindra, Nurhaliza Magfirah (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
Transparent, accountable, and efficient financial management is a key prerequisite for realizing quality public health services through Regional Public Service Agencies (BLUD). However, the reality in Sidenreng Rappang Regency (Sidrap) shows that most BLUD units, such as community health centers and hospitals, still face obstacles such as the absence of documented financial SOPs, low understanding of the preparation of Business and Budget Plans (RBA), and limited use of financial information systems. This community service activity aimed to improve the capacity of BLUD financial managers through training and technical assistance in preparing RBAs and SOPs in accordance with regulations, such as Permendagri No. 79 of 2018 and PP No. 23 of 2005. The implementation methods included identifying partner needs, interactive material presentations, group discussions, and the preparation of draft documents by participants. The results of the activity showed that 87% of participants were able to draft an initial RBA and understand the important elements of financial management SOPs. Participants also demonstrated an increased understanding of good governance principles, such as transparency and accountability. The final evaluation confirmed that the applied and case-based training approach was effective in building the technical competence of the apparatus. As a follow-up, it is recommended that further training be developed to cover accrual-based reporting and internal auditing, as well as the integration of digital financial systems. It is hoped that this activity will encourage a more adaptive and sustainable transformation of BLUD financial management and support the improvement of health service quality in Sidrap Regency.